PELATIHAN PEMANFAATAN DAN PEMASARAN PRODUK HOME INDUSTRY DI DESA KARANGJATI KECAMATAN SUSUKAN KABUPATEN BANJARNEGARA - Suryana Hendrawan; Taslim Immanudin; Irmawan Anang; Fatih Al Barid (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2019)
This service was carried out with the intention of being able to form the residents of Karangjati Village, Kec. Susukan Kab. Banjarnegara is an independent, creative and present entrepreneur. Many people in Karangjati Village actually have many products, but many of them stop in the production phase. To market their own products the majority are still participating in collectors or just waiting for orders. This service was carried out with training and mentoring methods to market community products that had been produced or had no ideas at all. In this training, initially the identification of what products have been produced by the residents will be carried out and the obstacles faced by the residents of Karangjati Village. This is done in the hope that training can be more conical to the main problems faced by citizens and can provide more appropriate solutions. After identification, training will be carried out on how to utilize existing technology and how to market the home industry products to the emerging online market. After this training, several people from Karangjati Village have directly practiced the results of their products to the simple On-Line market. Some existing products such as packaged versions of herbal medicine have also begun to be produced with more modern packaging. This increase in value products is expected to attract consumers' attention while increasing the economy of Karangjati Village residents.